Екоцид природного середовища України внаслідок російської агресії (за матеріалами доповіді на засіданні Президії НАН України 19 листопада 2025 р.) - Ходосовцев, О.Є. (Вісник НАН України, 2026)
За результатами польових досліджень, проведених у деструктованих війною екосистемах Дніпропетровської, Донецької, Запорізької, Київської та Херсонської областей, та подальшого аналізу експертних думок було сформульовано шість верифікованих критеріїв екоциду. Запропонована система критеріїв кваліфікації екоциду ґрунтується на п'яти ключових концептуальних ознаках: структурна відповідність, критичність існування, просторова локалізація, часова верифікація та альтернативна релевантність. Застосування цих критеріїв дозволить чітко відмежувати кримінальні правопорушення проти довкілля від тяжких міжнародних злочинів — кримінальних правопорушень проти миру, безпеки людства та міжнародного правопорядку, до категорії яких належить екоцид. Based on the results of field studies conducted in the war-destructed ecosystems of Dnipropetrovsk, Donetsk, Zaporizhzhia, Kyiv, and Kherson regions, and a subsequent analysis of expert opinions, six verified ecocide criteria were established (five biocentric and one anthropocentric). The proposed system for qualifying ecocide is based on five key conceptual features: structural consistency (alignment with the levels of living systems), criticality of existence (utilization of the IUCN ‘Endangered’ or ‘Critically Endangered’ categories), spatial localization (alignment with natural zones), temporal verification (a three-year monitoring period), and alternative relevance (the sufficiency of meeting at least one criterion). The application of these criteria will allow for a clear distinction between environmental crimes and grave international crimes — namely, crimes against peace, security of mankind, and international legal order, a category to which ecocide belongs.